(untitled) (Jurnal Pertanian Terpadu, 2019)
The purpose of this research was to determined the effect of straw compost and mulching on growth and yield of melon (Cucumis melo L.). This research was conducted in Garum Village, District of Garum, Blitar in August to November 2016. This research was conducted using a factorial randomize complete block design with 3 replications. The first factor was straw compost dose consists of three levels, i.e. k0: Without compost straw, k1: straw compost 10 tons/ha; k2: straw compost 20 tons/ha. Factor II was the type of mulch, consist of three levels, i.e. m0: Without mulch; m1: straw mulch; m2: silver black plastic mulch. From the two factors aboveobtained 9 combination of treatment. Observation of the plant include the length of the plant (cm), number of leaves (leaf), wet basic weigth and dry basic weight of plant (g), weight of fruit (kg), diameter of fruit (cm) and thickness of fruit (mm). Data were analyzed using Analysis of Variants (ANOVA) at 5% level, and if significantly followed by Duncan’s test at 5% level. Straw compost dose of 20 ton/ha can improve plant growth and better crop yield melon than without straw composttreatment. The increase in weight of melon with strawcompost treatment is 21.59%. Silver black plastik mulch treatment can increase the yield of melon up to 15.56% higher than without mulch treatment and improve 6.077% higher than the straw mulch treatment.